The effect of out of pocket (OOP) health expenditure on the budget shares of non-health commodities in Philippine households - Lim, Hans Ryan T.; Manotok, Josemaria Antonio T.; Mendoza, Maria Nimfa F. (Quezon City School of Economics, University of the Philippines Diliman, 2018)
This paper investigates whether out of pocket (OOP) health expenditures have a significant effect on the budget share allocation of 10 non-health commodities, namely food, education, recreation, transportation, alcohol, tobacco, clothing, housing and water, communication and durables for households in the Philippines. This is done using conditional Engel curves, which show how the budget share of a commodity increases or decreases in response to OOP health expenditures. Our findings suggest that poor households are most affected by rising OOP health expenditures. When OOP health expenditures rise, poor households are observed to decrease their budget shares of food, alcohol, tobacco, clothing, and communication, while their budget shares for housing and water and durables increase.
Thesis (B.S. Business Economics) -- University of the Philippines Diliman
Keywords: Households -- Philippines -- Finance; Medical care -- Philippines -- Finance; Out of pocket (OOP).